OPTIMAL SIGNAL-CODE CONSTRUCTIONS FOR INCREASE EFFICIENCY OF 5G AND 6G MOBILE INFOCOMMUNICATION RADIO SYSTEMS - VASYLKIVSKYI, MYKOLA; BOLDYREVA, OLHA; VARGATYUK, GANNA; BUDASH, MYHAILO (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article discusses methods of increasing the efficiency of information communication radio systems of mobile communication, which includes increasing spectral efficiency and energy efficiency when used for telecommunication radio equipment. A comparison of block error coefficient values for f-OFDM, W-OFDM and OFDM methods with mixed numerology of uplink and downlink subscriber channels of access to information resources of the telecommunications network was made. As a result of the study of compression methods using several carriers, the dominant compression method for mobile communication systems, in particular, the CP-OFDM method due to its high efficiency of spectrum use, scalability and flexibility due to the introduction of a cyclic prefix, has been determined.It is proved that the CP-OFDM compression method is free from the Doppler range shift problem, thus the range and Doppler shift estimations can be considered as independent tasks in CP-OFDM. In addition, CP-OFDM parameters such as carrier distance, guard interval size, frame length, and pilot shape can be tailored to optimize the performance and robustness of detection and data transmission. However, such advantages are based on perfect synchronization (time and frequency) between the transmitter and receiver - although perfect synchronization may not be possible, especially for bistatic scanning, where the transmitter and receiver of the scan signal are not adjacent. In this case, the cyclic prefix may not provide any advantage for quality scanning, and multiple unprefixed waveforms may be considered. The main disadvantage of rejecting the prefix is the difficulty of data detection (due to intersymbol interference), which must be eliminated. Another important challenge for scanning, where energy efficiency is extremely important, is the large PAPR of multi-carrier (prefixed or unprefixed) signals.Single-carrier compression methods, which are based on the expansion of the code area of common radar signals and communication, in which the radar characteristics are affected by sequence autocorrelation, have been studied. However, the long spreading code, which leads to good autocorrelation, reduces the spectrum utilization efficiency for communication systems. In this case, the estimation of the Doppler effect is not trivial and requires more complex algorithms. The justification of the choice of the signal modulation scheme in 5/6G radio systems has been made.
Keywords: downlink; uplink; ratio of peak power to average power; signal-code design; out-of-band radiation; signal compression method; Doppler range shift; intersymbol interference; signal modulation scheme